STRATEGIC MARKERS OF INVESTMENT IN CRITICAL INFRASTRUCTURE OBJECTS IN THE CONTEXT OF THE ECONOMIC SECURITY OF UKRAINE - Zatonatskiy, Dmytro; Poltoratska, Alona (Socio-economic relations in the digital society, 2024)
The paper examines the strategic aspects of investing in Ukraine’s critical infrastructure in the state’s economic security context. The importance of critical infrastructure for the stable functioning of the economy in the face of modern challenges, including military threats, cyber-attacks and natural disasters, is analyzed. The issue of financial instability, which requires the involvement of private investors and international partners to restore and modernize infrastructure, is also considered separately. The study examines the role of public-private partnership and international cooperation as the introduction of innovative technologies, such as artificial intelligence and IoT, to increase the efficiency and sustainability of infrastructure facilities. Critical strategies for effective risk management and attracting investments to restore energy, transport and communications have been identified. Recommendations are offered for assessing investments’ economic and social efficiency, considering the payback and impact on the population’s well-being. The paper also outlines the prospects for long-term economic growth through investment in critical infrastructure, an essential element of the country’s post-crisis recovery. This study delves into the strategic dimensions of investing in Ukraine’s critical infrastructure, emphasizing its significance for economic security. The paper thoroughly examines Ukraine’s financial constraints due to the ongoing war and economic instability. It underscores the necessity of engaging private investors and fostering international collaboration. Public-private partnerships (PPPs) and international financial institutions are identified as crucial players in providing the necessary funding and expertise for the recovery and modernization of infrastructure. The article also explores how integrating innovative technologies, such as artificial intelligence (AI) and the Internet of Things (IoT), can significantly enhance the resilience and efficiency of infrastructure systems. In conclusion, the article offers strategic recommendations for investing in Ukraine’s critical infrastructure. The purpose of the study is to identify strategic priorities for the allocation of investment resources for the reconstruction of critical infrastructure, considering the aspects of economic security.